Psychosocial Factors and the Care Cascade for Hepatitis C Treatment Colocated at a Syringe Service Program. (2nd September 2020) - Winetsky, Daniel; Burack, Daniel; Antoniou, Pantelis; Garcia, Bill; Gordon, Peter; Scherer, Matthew
Abstract: Background: Direct-acting antiviral (DAA) therapy for hepatitis C virus (HCV) is highly effective. However, people who inject drugs face significant barriers to DAA access. Methods: We describe a program that colocates HCV management within a syringe service program in New York City. We performed a retrospective chart review of all patients with confirmed HCV viremia. Results: From 2015 to 2018, 102 patients with viremia completed intake. Fifty-eight patients started DAAs. Nine patients discontinued treatment or were lost to follow-up before completion; 1 is continuing DAA treatment. Of 48 patients who completed therapy, sustained virologic response (SVR) was achieved in 43 (89.6%). Age and established mental health treatment at intake were associated with SVR. Regular cocaine use was negatively associated with SVR in univariate analysis, but this association was not significant after adjustment for age. Of 30 patients completing DAA therapy with active illicit opioid use at intake, 14 (46.4%) engaged in opioid use disorder (OUD) treatment during therapy, and 9 remained in OUD treatment after completion of DAA treatment. Conclusions: Loss to follow-up is a challenge for people who inject drugs, but among those who completed treatment, SVR was achieved at a high rate. Mental health treatment may facilitate HCV cure. Conversely, HCV therapy may facilitate engagement in OUD treatment and other services.